Characterization of the anodic growth and dissolution of oxide films on valve metals - Linarez Pérez, Omar Ezequiel (2008)
Chemical dissolution processes coupled to anodic oxide growth taking place by a "high-field" conduction mechanism, are considered. The equation for the steady-state current density obtained during potentiodynamic polarization measurements is derived and the effect of the oxide dissolution rate on the overall potentiodynamic behaviour by applying repetitive scans with either fixed or increasing anodic switching potentials is discussed. The procedure for obtaining the current dissolution as well as the parameters that characterize the high-field growth is discussed.